(untitled) (Journal of Human Sciences, 2023)
The current research aims to reduce the traits of aggression among juvenile delinquents by revealing the effectiveness of a cognitive - behavioural counselling treatment program. The change that occurs in the case is due to the effectiveness of the program used. In addition, the researcher adopted the descriptive analytical approach to describe the clinical changes that occur on the case. The case was a delinquent male, aged 15 years, studying in the ninth grade of basic education, in good health and not suffering from any sensory, motor or mental disability and at a somewhat low economic level, living with his parents, the mother is a housewife. The researcher also relied to collect data on tools such as interview and observation of all kinds, self-reports and reports of others about the situation, grade scales, write-off lists, monitoring tables, daily records and psychological scales, in addition to the therapeutic counselling program (prepared by the researcher). The most important results of the research were an acceptable decrease in the severity of behaviours, the targeted modification and the accompanying emotions, and the child became more interactive with others in the social and school environment. An improvement in his relationship with his brothers and colleagues was noted and a good decrease in the traits of aggressive behaviour, this improvement continued for more than a month, This improvement continued for more than a month.